2008
DOI: 10.1111/j.1439-0272.2008.00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Triorchidism: a case report and review of similar conditions

Abstract: Polyorchidism is a rare anomaly, defined as the presence of more than two testicles with about 100 cases reported in the literature. The majority of cases were triorchidism with occasional bilateral duplication. We report the case of a 32-year-old man with polyorchidism, presenting with primary infertility with oligoasthenoteratozoospermia semen profile. Scrotal examination revealed two discrete ovoid nontender, firm, mobile lumps with testicular sensation in the right side of the scrotum. Ultrasonography and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…[2,9] Although previous reports suggested that most patients with polyorchidism presented with painless testicular or groin masses, recent analyses revealed that cases were mainly encountered during evaluation for other symptoms, such as acute scrotal pain or infertility. [2,[4][5][6] Our case presented with a painless scrotal lump, whereas most cases in the literature were diagnosed during exploration for inguinal hernia (24%), undescended testis (22%), and testicular torsion (15%). [2] Only 7% presented with pain as the solitary symptom.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…[2,9] Although previous reports suggested that most patients with polyorchidism presented with painless testicular or groin masses, recent analyses revealed that cases were mainly encountered during evaluation for other symptoms, such as acute scrotal pain or infertility. [2,[4][5][6] Our case presented with a painless scrotal lump, whereas most cases in the literature were diagnosed during exploration for inguinal hernia (24%), undescended testis (22%), and testicular torsion (15%). [2] Only 7% presented with pain as the solitary symptom.…”
Section: Discussionmentioning
confidence: 77%
“…Although there are no clear guidelines to determine which cases can be followed conservatively, recent data support watchful waiting in the absence of concomitant abnormalities and if testicular malignancy can be ruled out safely. [2,[4][5][6] In contrast, surgical exploration has the advantage of fixing the testis to prevent torsion and making biopsy easier if indicated. [3,4,9,11] Further management depends on several factors, such as the position of the supernumerary testis [ie, orthotopic (scrotal) vs. ectopic (inguinal or abdominal)], the reproductive potential (whether it is attached to a draining epididymis and vas), its size and volume (normal or atrophic), the age of the patient (young or adult), and psychological aspects that are related to follow-up (ie, anxiety of the patient).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations